Netter's cardiology - Runge, Marschall Stevens; Ohman, Magnus; Netter, Frank H (Icon Learning Systems, 2004)
With coverage on virtually every topic in cardiovascular medicine, the authors have distilled massive amounts of information down to the most needed facts, using Netter artwork to illustrate the most salient points and bring the information to life. Readers get quick access to essential information for diagnosis and treatment of most cardiovascular problems. Concise chapters provide depth and insight into complex medical problems for accurate diagnosis and selection of therapy using the latest technology and therapeutic approaches.
Keywords: kardiologie; Cardiology